Three‐year results of visual outcome with disease activity–guided ranibizumab algorithm for the treatment of exudative age‐related macular degeneration. (14th June 2012) - Lala, Ceklic; Framme, Carsten; Wolf‐Schnurrbusch, Ute E. K.; Wolf, Sebastian
Abstract: Purpose:  To evaluate 3‐year follow‐up treatment outcomes with ranibizumab (Lucentis ® ) 0.5 mg administered either monthly or quarterly on a pro re nata (PRN) basis according to a disease activity–guided monitoring and treatment algorithm. Methods:  A total of 316 treatment‐naive eyes of 316 patients with exudative age‐related macular degeneration met the criteria for inclusion in this retrospective, interventional case series. Patients were treated with ranibizumab 0.5 mg according to a disease activity–guided algorithm with monthly monitoring. Optical coherence tomography and fluorescein angiography were routinely used to assess disease activity: active lesions were treated with a series of three monthly injections, whereas inactive lesions were treated with quarterly injections. Results:  Mean Early Treatment Diabetic Retinopathy Study best‐corrected visual acuity improved from 52 letters at baseline to 59 letters at 12 months, achieved with a mean of 7.1 injections, 61 letters at 24 months with a mean of 5.0 injections administered in the second year and 60 letters at 36 months with a mean number of 5.2 injections. Conclusions:  Monthly visits and a morphology‐driven PRN regimen with 3 injections in case of recurrence plus quarterly injections in case of inactive CNV resulted in an average VA gain of 7–9 letters that could be maintained over 3 years.